A note on (t - 1)-chromatic Ramsey number of linear forests. Issue 2 (2nd April 2020) - Khamseh, Amir
Abstract : Given t distinct colors, we order the t subsets of t −1 colors in some arbitrary manner. Let G 1, G 2, …, G t be graphs. The ( t − 1 ) -chromatic Ramsey number, denoted by r t − 1 t ( G 1, G 2, …, G t ), is defined to be the least number n such that if the edges of the complete graph K n are colored in any fashion with t colors, then for some i the subgraph whose edges are colored with the i th subset of colors contains a G i . In this paper, we study the ( t − 1 ) -chromatic Ramsey number of linear forests.